1988
DOI: 10.1038/hdy.1988.110
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio evolution in lemmings

Abstract: In the varying lemming, Dicrostonyx torquatus, numerous XY females occur due to the X-linked mutation X. Gileva (1987) has shown that there is also segregation distortion in males, with the segregation ratio for V sperm being about O•56, which has a significant effect on the sex ratio and the frequency of XV females. A theoretical analysis shows that this degree of segregation distortion is expected to evolve in the Dicrostonyx system under random mating, provided that reproductive compensation for the loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 6 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…In situations of colonization, female number is a limiting factor to demographic expansion, and female‐biased sex‐ratios could be favored. X‐borne factors biasing the sex‐ratio in favor of females have been described, acting either as transmission distorters (Montchamp‐Moreau and Cazemajor 2002; Montchamp‐Moreau 2006; Tao et al 2007) or as feminizing factors (Givela 1987; Bulmer 1988; Liu et al 1998; Veyrunes et al 2010). The possibility that the introgressed X‐chromosome fragment be linked to a sex‐ratio distorter relates to a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…In situations of colonization, female number is a limiting factor to demographic expansion, and female‐biased sex‐ratios could be favored. X‐borne factors biasing the sex‐ratio in favor of females have been described, acting either as transmission distorters (Montchamp‐Moreau and Cazemajor 2002; Montchamp‐Moreau 2006; Tao et al 2007) or as feminizing factors (Givela 1987; Bulmer 1988; Liu et al 1998; Veyrunes et al 2010). The possibility that the introgressed X‐chromosome fragment be linked to a sex‐ratio distorter relates to a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, heterogametic and homogametic females showed a similar litter size at birth. A compensation of litter size may arise from an "automatic" property of the reproductive system, due to reduced competition between surviving embryos as a result of the early loss of YY* zygotes, or an "evolved" property, due for example to an increased ovulation rate in XY* females (BULL and BULMER 1981;BULMER 1988). Our observations on the number of corpora lutea at mid-gestation showed similar mean values for XX and XY* females, which means that there is no increase in the ovulation rate of heterogametic females of A .…”
Section: Discussionmentioning
confidence: 99%
“…However, reasons due to the evolutionary history of the species should not be neglected. For instance, in the case of the wood lemming, BULMER (1988) suggested that the occurrence of the X* chromosome is due to a historical "accident" and its persistence in lemming populations is possible only because no suppressor has yet evolved.…”
Section: Sex Ratiomentioning
confidence: 99%